1996
DOI: 10.14341/probl11890
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function during prolonged exposure to fluorides

Abstract: Thyroid function was examined in 165 workers of electrolysis shops of aluminum production with more or less expressed signs of chronic fluoride intoxication (fluorosis) by radioimmunoassay of hormones and the test of 13II absorption by the thyroid. The detected thyroid abnormalities were characterized by a moderate reduction of iodine-absorbing function of the thyroid, low T3 with normal T4 level, and a slight increase of TTH concentration. These changes augmented with longer service and fluorosis progress. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Further studies conducted in China, also found that excessive F exposure inhibited thyroid iodine uptake in children [10]. Similar effects were observed in a Russian study examining the effects of occupation exposure to F among subjects with signs of chronic fluorosis [18]. Consistent with these findings, a recent all Ireland study which measured iodine status in adolescent girls throughout the island of Ireland; which includes the Republic of Ireland (RoI) and Northern Ireland (NI), found that median UIC’s were significantly lower in adolescent girls in all participating locations in the RoI compared to NI.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Further studies conducted in China, also found that excessive F exposure inhibited thyroid iodine uptake in children [10]. Similar effects were observed in a Russian study examining the effects of occupation exposure to F among subjects with signs of chronic fluorosis [18]. Consistent with these findings, a recent all Ireland study which measured iodine status in adolescent girls throughout the island of Ireland; which includes the Republic of Ireland (RoI) and Northern Ireland (NI), found that median UIC’s were significantly lower in adolescent girls in all participating locations in the RoI compared to NI.…”
Section: Introductionsupporting
confidence: 58%
“…As previously elucidated, Tg has been found to play a crucial role in downregulating NIS expression. There is robust evidence from epidemiological studies conducted in different geographic regions to show that F exposure increases TSH levels in humans [12,15,18,29,35,165,166,167,168,169,170,171,172,173,174,175,176,177,178]. Since TSH stimulates thyroid follicular cells to produce Tg [179,180]; serum Tg concentrations are typically higher in individuals with a raised TSH or primary hypothyroidism [181].…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 99%
“…An analysis of immune status showed that T-lymphocyte count enhanced, but the cells were nonfunctional due to reduced FT 3 levels 21 . In yet another Russian report, amongst industrial workers exposed to Fand suffering from industrial fluorosis, aberration in the thyroid gland function was reported 22 .…”
Section: Human Subjects On Consumption Of Fin Excessmentioning
confidence: 99%
“…The second objective of the present review is to highlight the implications of diseases caused by excess fluoride and iodine deficiency and the synergy of these two elements in a biological system. There are nine studies from India [7][8][9][10][11][12][13][14][15] and another eight studies from other nations [16][17][18][19][20][21][22][23] reported on goitre prevalence in populations with iodine sufficiency, goitre in fluoride endemic areas and goitre in industrial workers exposed to fluorine fumes and dust. These studies have been described in the section dealing with human studies.…”
mentioning
confidence: 99%
“…In Delhi, India, from a group of 90 children with dental fluorosis living in areas with endemic fluoride, not iodine deficient, 54.4% had well-defined hormonal disorders (Susheela et al 2005). Other studies in China and Russia corroborate the relation fluoride/hypothyroidism with changes in thyroid hormones, including reduced T3 and increased TSH, in populations exposed to high levels of fluoride in the workplace or in water (Bachinskii et al 1985;Mikhailets et al 1996). Zhao et al (1998)…”
Section: Evaluation Of T3 and T4 Parameters And Total Antioxidant Capmentioning
confidence: 80%